2018
DOI: 10.24925/turjaf.v6i5.602-606.1838
|View full text |Cite
|
Sign up to set email alerts
|

Holstein İneklerde GH/AluI Polimorfizmi ile Bazı Süt Verim Özellikleri Arasındaki İlişkiler

Abstract: Bu çalışmanın amacı, organik yetiştirilen 115 baş Holstein ırkı inekten oluşan sürüde Büyüme Hormon (GH) geni bakımından genotip ve allel frekanslarınının dağılımını belirlemek, genetik varyasyonu ortaya koymak ve bazı süt verim özellikleri arasındaki ilişkileri araştırmaktır. Elde edilen bulgular sonucunda, çalışılan sığır populasyonunun GH geni LL, LV ve VV genotip frekanslarının sırasıyla 0,41, 0,49, ve 0,10 olarak bulunduğu ve Hardy-Weinberg eşitliği testine göre dengede olduğu görülmüştür. Laktasyon süt v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Pal et al [14] showed that crossbred males with the bGH-AluI LL genotype demonstrated higher expected milk productivity. It was shown in other studies on Holstein cows that the total milk yield in animals with the bGH-AluI LV and bGH-AluI VV genotypes was significantly higher than in cows with the bGH-AluI LL genotype, which suggests the dominance of the bGH-AluI V allele [15][16][17][18]. Our results also showed that black-and-white cows with the bGH-Alu-I LV genotype have higher milk yield.…”
Section: Discussionsupporting
confidence: 72%
“…Pal et al [14] showed that crossbred males with the bGH-AluI LL genotype demonstrated higher expected milk productivity. It was shown in other studies on Holstein cows that the total milk yield in animals with the bGH-AluI LV and bGH-AluI VV genotypes was significantly higher than in cows with the bGH-AluI LL genotype, which suggests the dominance of the bGH-AluI V allele [15][16][17][18]. Our results also showed that black-and-white cows with the bGH-Alu-I LV genotype have higher milk yield.…”
Section: Discussionsupporting
confidence: 72%
“…In two different studies in which we correlated the yields of GH/AluI gene polymorphisms in 118 and 186 numbers of Holstein cattle breeds from different farms, no significant relationship was found between genotypes and milk yields. A similar relationship could not be found between GH-AluI and IGFI-Sna-BI gene polymorphisms and milk yield in Simmental cattle (Sönmez et al, 2018;Özdemir et al, 2018). Therefore, considering our three association studies, we examined previous studies to determine the potential for these gene regions to be used as markers.…”
Section: Discussionmentioning
confidence: 90%
“…The bovine GH gene is located on chromosome 19q and contains four introns and five exons. GH is considered a candidate gene associated with growth, milk and reproduction traits (Curi et al, 2006;Dario et al, 2005;Grochowska et al, 2001;Pereira et al, 2005;Sönmez et al, 2018). Researchers have identified several polymorphisms in the GH gene (Amiri et al, 2018;Bordonaro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%